Unveiling Diaconal Practices and Discourse in Asia: The Role of WCC in Shaping Human Rights Advocacy into the Ecumenical Movement - Soto, I.; Zeferino, J. (University of jaffna, 2024)
The World Council of Churches (WCC) embraces a language of human rights since its foundation. In 1948, WCC, through its Commission of the Churches on International Affairs, contributed with aspects about freedom of religion on the Universal Declaration of Human Rights, this being instrumental to formulate its 18th Article which evolved into a pivotal cornerstone advocating for religious freedom on a global scale. Nowadays, it is known that through an ecumenical advocacy, WCC has a human rights programme that supports engagement of member churches and partners in reporting mechanisms of the UN human rights system, while emphasising the importance of protecting human dignity through diaconal practices. However, despite these efforts, as stated by a WCC Statement on the Universal Declaration of Human Rights issued in 2008, the council acknowledges a gap between rhetoric and action, noting progress in normative aspects, yet underscoring the shortfall in translating promises into effective actions. Thus, this paper seeks to understand how WCC sides with human rights grammar through its adoption of concepts presented in the Universal Declaration of Human Rights, outlining the introduction of a practical diaconal language at the 2013 10th Assembly of the World Council of Churches in Busan, Republic of Korea. During this assembly, discussions focused on the WCC’s plans, theological reflections and issues to achieve just peace. Through a Critical Discourse Analysis, this paper examines the assembly’s development of a diaconal language, intertwining it with the ecumenical movement. It also delves into theoretical perspectives, discursive practices, and diaconal activities, portraying the commitment of WCC member churches to further human rights efforts for just peace, especially considering the Asian context.
Keywords: World council of churches; Asian churches; Ecumenism; Critical discourse analysis; Public theology